Mobile Health in IBD: Enhancing Care, One Phone at a Time. Issue 2 (1st November 2019) - Chang, Shannon; Hamilton, Matthew; Lees, Charlie; Atreja, Ashish
Abstract : Opportunities exist within mobile health to improve care for IBD patients. In this review, we highlight features of several original IBD digital health platforms and suggest ideal features of an application that will optimize IBD care for patients and providers.